Development of The Delivery Assistance Module as an Innovation to Facilitate Delivery in the Archipelago - Nurniati Tianastia Rullyni; Utami Dewi; Rahmadona Rahmadona (Alliance oh Health Activists (AloHA), 2022)
The family's active role during labor as an act of maternal love can reduce the incidence of labor complications and achieve safe delivery. This study aimed to determine the effect of the delivery companion module on the duration of labor in women giving birth in the archipelago region. The design in this study used a quasi-experimental with post-test only control group design. The sampling technique uses the hypothesis test of two independent population means of 34 maternal mothers. The research was conducted at the Bidan Praktik Mandiri (BPM) in Tanjungpinang City, from March to May 2022. The research tools used were observation sheets and partographs. To determine whether there is an influence of the independent variable and the dependent variable, statistical analysis of the Independent Sample t-Test is used. The results showed a significant effect of the delivery companion module on the length of labor in normal delivery mothers (p=0.00). Labor accompanied by a husband with a delivery companion module can shorten the delivery process compared to without a delivery companion module. Using the delivery companion module as a health promotion media is recommended to shorten the delivery process. Keywords: module childbirth assistant; length of labor